Cr(OH)3-NPs-CNC hybrid nanocomposite: a sorbent for adsorptive removal of methylene blue and malachite green from solutions - Nekouei, F.; Nekouei, S.; Keshtpour, F.; Noorizadeh, H.; Wang, Shaobin (Springer, 2017)
© 2017 Springer-Verlag GmbH Germany In this article, Cr(OH) 3 nanoparticle-modified cellulose nanocrystal (CNC) as a novel hybrid nanocomposite (Cr(OH) 3 -NPs-CNC) was prepared by a simple procedure and used as a sorbent for adsorptive removal of methylene blue (MB) and malachite green (MG) from aqueous solution. Different kinetic models were tested, and the pseudo-second-order kinetic model was found more suitable for the MB and MG adsorption processes. The BET and Langmuir models were more suitable for the adsorption processes of MB and MG. Thermodynamic studies suggested that the adsorption of MB and MG onto Cr(OH) 3 -NPs-CNC nanocomposite was a spontaneous and endothermic process. The maximum adsorption capacities for MB and MG were reached 106 and 104 mg/g, respectively, which were almost two times higher than unmodified CNC. The chemical stability and leaching tests of the Cr(OH) 3 -NPs-CNC hybrid nanocomposite showed that only small amounts of chromium were leached into the solution.